Decolonisation and Gender: Perspectives on Literatures and Cultures of the Americas - Romana Radlwimmer (Gender a Výzkum)
In the recent past, decolonial proposals have become more and more important for feminisms of the Americas, that is, for Latin American and U.S. Latina/o theories and practices negotiating the significance of gender. Decolonial feminist thought proposes multiple ways of deconstructing coloniality (the ongoing effects of colonisation), and distances itself from postcolonial feminisms by emphasising not only its own unique, historically diverse geopolitical situatedness in the Americas, but also discordance with the assumption of the postcolonial “silenced subaltern female subject”. The article traces some of the conceptual travels of a decolonial feminist project as it is, today, under construction, and ponders on the options it presents for literary and cultural studies of the Americas on a transborder level. It then presents two decolonial feminist theoretical proposals: María Lugones’ Coloniality of Gender and her attempt to move, as she says, toward a decolonial feminism, as well as Gloria Anzaldúa’s concepts of Borderlands and Nepantla. Lugones analyses “gender” as an inherently colonial category which defines an ecological, economic, political, spiritual, and epistemological modernity for the Americas; Anzaldúa envisions a world of decolonial, feminist poetical interstices while employing creative practices. These notions reshape the tools available for future cultural and literary analysis and propose a holistic politics of healing.